MAPEAMENTO FÍSICO DOS GENES serk 2, svp-like E mdar 4 EM Carica papaya - Dornela, Adeilson Frias (2022)
Cytogenomics is based on physical mapping and provides data about the organization and structure of the genome. Physical mapping of specific DNA sequences along chromosomes is possible through fluorescent in situ hybridization (FISH). Cytogenomics in C. papaya has been developed using BAC-FISH, and repeatome sequences, as the rDNA genes. Despite the advances in cytogenomic studies in plant species, physical mapping has not been conducted from single-copy and/or few number-copy genes. Thus, we aimed to map the serk 2, svp-like and mdar 4 genes in C. papaya mitotic chromosomes. The sequence of the three genes was amplified, and the amplicons sequenced, confirming the homology in relation to serk 2, svplike and mdar 4 genes. C. papaya diploidy was confirmed, since all karyotypes showed 2n = 2x = 18 chromosomes, and nuclear 2C DNA content of 0.75 ± 0.016 pg. The mitotic chromosomes were classified as metacentric (chromosomes 1, 5, 7 and 8) and submetacentric (chromosomes 2, 3, 4, 6 and 9), with a total length variation of 4.32 ± 1.53 µm (chromosome 1) to 2.70 ± 0.42 µm (chromosome 9). Using the same FISH procedure, we mapped gene sequences from 251 to 1,166 base pairs. The serk 2 gene was mapped in the interstitial portion of the chromosome 1 long arm, and the interphase nuclei showed two clear fluorescence signals. Considering the sequencing data from the C. papaya sex chromosomes (X and Y), the svp-like and mdar 4 genes were mapped in the interstitial region of the X chromosome long arm. Both genes showed only one fluorescence signal in the interphase nuclei. Therefore, the results evidence genetic differences between the X and Y sex chromosomes of C. papaya, contributing with new data about the structure and evolution of these chromosomes. We point that svp-like and mdar 4 are also genes useful as a cytomolecular marker for early sex determination. In addition, the protocol adopted here can be reproduced for other single-copy and/or low-copy genes, allowing the mapping and construction of cytogenetic maps.